Research progress and prospect of postoperative adjuvant therapy for resectable intrahepatic cholangiocarcinoma - Sun, Yanxin; Jiang, Wei; Duan, Ruiheng; Guan, Lianyue (Frontiers in Pharmacology, 2024)
Intrahepatic cholangiocarcinoma (ICC) is the second most common primary malignancy of the liver, following hepatocellular carcinoma (HCC). Surgical resection remains the only potentially curative treatment for ICC. However, due to its high malignancy and propensity for postoperative recurrence, the prognosis for ICC is generally poor, and there is currently little standardized approach for adjuvant therapy following curative surgery. This article aims to explore adjuvant treatment strategies for ICC post-curative surgery by reviewing retrospective studies and clinical trials conducted in recent years. The analysis focuses on the effectiveness, challenges, and potential developments in the management of ICC post-surgery, considering the high recurrence rates and the need for improved therapeutic approaches to enhance patient outcomes. Additionally, we discuss the various types of adjuvant treatments that have been explored, including chemotherapy, radiation therapy, and targeted therapies. The goal is to provide a comprehensive overview of the current landscape and highlight promising directions for future research to improve survival and quality of life for ICC patients.